Is more competition better? Retail electricity prices and switching rates in the European Union. (October 2022) - Amenta, Carlo; Aronica, Martina; Stagnaro, Carlo
Abstract: The European Union (EU) promotes the liberalization of retail electricity markets to achieve lower prices, diversified offers, greater customer participation, and sustainable consumption behaviours. While retail competition has been a reality in most EU member states, most studies find that retail competition is suitable for large customers, but the evidence on small customers is inconclusive. We analyze data on electricity prices and switching rates in 27 EU member states and the UK from 2000 to 2019. We find that retail competition is associated with lower prices and that the effect of full liberalization is greater than that of partial liberalization.